2009
DOI: 10.1183/09031936.00172008
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 7 function is reduced in adolescents with asthma

Abstract: Anti-viral innate immune responses may be impaired in asthma, although the mechanisms are not well understood. Toll-like receptors (TLRs) 7 and 3 are particularly relevant for initiating responses to common respiratory viruses, as they recognise single-stranded viral RNA and double-stranded viral RNA, respectively. The aim of the present study was to investigate TLR7 and TLR3 function in 14-yr-old adolescents with asthma.Blood mononuclear cells obtained from 17 atopic asthmatics, 29 atopic, non-asthmatics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
84
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(94 citation statements)
references
References 32 publications
9
84
1
Order By: Relevance
“…Cell separation and culture PBMC were isolated from heparinized blood by density gradient centrifugation, as previously described (13), and cultured at 1 3 10 6 PBMC in 24 culture plates together with RV16 at a multiplicity of infection of 5. Control cultures contained medium alone.…”
Section: Rv Generation and Titrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell separation and culture PBMC were isolated from heparinized blood by density gradient centrifugation, as previously described (13), and cultured at 1 3 10 6 PBMC in 24 culture plates together with RV16 at a multiplicity of infection of 5. Control cultures contained medium alone.…”
Section: Rv Generation and Titrationmentioning
confidence: 99%
“…RV-stimulated alveolar macrophages from asthmatics produce less IFN-l than alveolar macrophages from healthy individuals (7). PBMC from asthmatic children and adults secrete less IFN-a following in vitro exposure to viruses (11,12), and this is associated with reduced function of TLR7, the receptor for viral ssRNA (13). Plasmacytoid dendritic cells (pDC) are a potent source of type-I IFN synthesis during virus infections (14), and numerical changes in circulating pDC have been linked both to asthma development in young children (15) and to established asthma in adults (16).…”
mentioning
confidence: 99%
“…A role for TLR7 in the development of virus-induced airway hyperreactivity has been proposed, because TLR7 activation causes a proinflammatory type 1 T-helper cell (Th1) immune response (8) and because TLR7 polymorphisms have been associated with asthma (9). In patients with asthma, however, TLR7 responses were reduced (10). Furthermore, in mouse models of allergic airway inflammation, the TLR7 imidazoquinoline agonists imiquimod (R837) and resiquimod (R848) reduced airway hyperreactivity, airway eosinophilia, goblet cell hyperplasia, and smooth muscle hypertrophy (11)(12)(13)(14), whereas TLR7 knockout mice were prone to the development of asthma-like airway pathology after pneumovirus infection (15).…”
mentioning
confidence: 99%
“…TLR7 is expressed in natural killer T cells (NKT) which are capable of secretion of interferon γ that supports the development of Th1 response [17]. Moreover, it has been shown that adolescents with asthma have reduced TLR7 function that possibly increases their susceptibility to viruses causing respiratory diseases [18].…”
Section: Toll-like Receptors and Allergic Asthmamentioning
confidence: 99%